2019
DOI: 10.1002/mrd.23171
|View full text |Cite
|
Sign up to set email alerts
|

The implication of single‐nucleotide polymorphisms in ovarian hyperstimulation syndrome

Abstract: Ovarian hyperstimulation syndrome (OHSS) is an undesirable complication in the course of ovarian stimulation. This kind of stimulation is aimed at acquiring a sufficient number of high‐quality oocytes in in vitro fertilization (IVF). Whereas the predisposition to OHSS could be impacted by genetic polymorphisms in susceptible genes, the present study has been jointly conducted with an Iranian cohort to scrutinize its relevant implication. Genomic DNA was extracted from blood samples of patients with a normal ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
(63 reference statements)
1
3
0
Order By: Relevance
“…These findings could be in agreement with previous data demonstrating a higher sensitivity of women with A/A genotype or A-allele of LHCGR rs2293275 to the FSH stimulation [26][27][28]. In a recent study, however, we addressed a significant association between rs2293275 G-allele and OHSS, indicating the implication of this variation as a risk factor for developing OHSS [29]. Considering these findings, it may be noteworthy that this variation may render a dual effect on altering the sensitivity Involvement of folate deficiency and hyperhomocysteinemia in reproduction and an association between MTHFR polymorphisms and pregnancy complications and birth malformations has so far been reported [30,31].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings could be in agreement with previous data demonstrating a higher sensitivity of women with A/A genotype or A-allele of LHCGR rs2293275 to the FSH stimulation [26][27][28]. In a recent study, however, we addressed a significant association between rs2293275 G-allele and OHSS, indicating the implication of this variation as a risk factor for developing OHSS [29]. Considering these findings, it may be noteworthy that this variation may render a dual effect on altering the sensitivity Involvement of folate deficiency and hyperhomocysteinemia in reproduction and an association between MTHFR polymorphisms and pregnancy complications and birth malformations has so far been reported [30,31].…”
Section: Discussionsupporting
confidence: 93%
“…Based on the distribution of genotypes or alleles in our study, this polymorphism is not implicated in the COS outcome of women undergoing an IVF procedure in terms of releasing oocytes. Recently, we could show a protective effect of A-allele at the locus of PGR rs10895068 variation in developing OHSS [29]. Hence, although this polymorphism seems to be associated with preventing ovarian from overreacting to FSH stimulation, it does not influence diminished ovarian response.…”
Section: Discussionmentioning
confidence: 87%
“…Genetic variants in patients developing severe OHSS may provide further insight into the mechanisms involved in the syndrome. Known and frequent polymorphisms in genes predisposing to OHSS have been described (i.e., FSHR, LHR, CYP11A, AMH, VEGFR2) [13]. Recently, the VEGF receptor, VEGFR3 (official name FLT4) has been suggested to have a role in OHSS.…”
Section: Introductionmentioning
confidence: 99%
“…A case series performing whole-exome sequencing (WES) in four patients with severe OHSS after GnRHa trigger and freeze all, identified rare variants in this gene in two out of four patients [14]. Comparison of singlenucleotide polymorphisms (SNPs) in genes suggested to be involved in OHSS (MTHFR, AMHR2, LHCGR, PGR, SERPINE1) between 100 OHSS patients and 100 normal responders suggested that polymorphisms of MTHFR, AMHR2, and LHCGR genes could promote the risk of susceptibility to OHSS [13]. As overlap in variants in specific genes has been minor or absent in OHSS cases published, we here added a broader approach by also focusing on possible pathways influenced by the genetic variants.…”
Section: Introductionmentioning
confidence: 99%